In-Hospital Delays in Stroke Thrombolysis: Every Minute Counts. Issue 8 (August 2020) - Darehed, David; Blom, Mathias; Glader, Eva-Lotta; Niklasson, Johan; Norrving, Bo; Eriksson, Marie
Abstract : Background and Purpose: Intravenous thrombolysis is a well-established treatment for acute ischemic stroke. Our aim was to quantify the effect of each minute delay in door-to-needle time (DNT) on 90-day survival, intracerebral hemorrhagic complication <36 hours, and functional outcomes at 3 months, in routine clinical practice. Methods: Our nationwide registry-based study included 14 132 adult patient admissions with ischemic stroke receiving intravenous thrombolysis from 2010 to 2017. Outcomes were analyzed using multivariable logistic regression, adjusting for potential confounders. Results: Median DNT was 47 minutes, with an improvement from 65 to 38 minutes during the study. Median age was 74 years, and median National Institutes of Health Stroke Scale 8 points. We found a significant impact of each minute delay in DNT with reduced odds of survival by 0.6%, increased odds of intracerebral hemorrhagic and worse activities of daily living by 0.3%, and worse living conditions and mobility by 0.4%. Conclusions: Improving DNT is a key factor in achieving good outcomes after stroke. We estimate that in Sweden alone in 2017, compared with 2010, the shorter DNT achieved have saved 38 lives, avoided 8 intracerebral hemorrhagic transformations, and spared, respectively, 36, 51, and 52 patients from a worsening in activities of daily living, living conditions, and mobility. DNT is sensitive for interventions and should be targeted in quality improvement efforts. Abstract : Supplemental Digital Content is available in the text.